External beam radiotherapy for unresectable hepatocellular carcinoma, an international multicenter phase I trial, SAKK 77/07 and SASL 26. Issue 1 (December 2017) - Herrmann, Evelyn; Naehrig, Diana; Sassowsky, Manfred; Bigler, Martin; Buijsen, Jeroen; Ciernik, Ilja; Zwahlen, Daniel; Pellanda, Alessandra; Meister, Andreas; Brauchli, Peter; Berardi, Simona; Kuettel, Erika; et al.
Abstract Purpose To assess feasibility and safety of conventionally fractionated radiotherapy (cfRT) in patients with hepatocellular carcinoma (HCC). Methods Patients with histologically confirmed stage cT1-4, cN0-1 HCC and Child-Pugh Score (CPS) A or B disease were included in a phase I multicenter trial. Metastatic HCC were allowed if ≥90% of total tumor volume was located within the liver. Patients were enrolled onto five dose-escalation levels (54–70Gy in 2Gy fractions) based on a modified 3 + 3 design, with cohorts of five patients instead of three patients in dose levels 4 and 5. Primary trial endpoint was dose-limiting toxicity (DLT), as specifically defined for 17 clinical and nine laboratory parameters as grade ≥3 or ≥4 toxicity (CTCAE vs. 3). The threshold to declare a dose level as maximum tolerated dose (MTD) was defined as a DLT rate of ≤16.7% in dose levels 1–3, and ≤10% in dose levels 4–5. Best objective response of target liver lesions and adverse events (AE's) were assessed as secondary endpoints. Results The trial was terminated early in DL 3 due to low accrual. Nineteen patients were recruited. Fifteen patients were evaluable for the primary and 18 for the secondary endpoints. Maximum tolerated dose was not reached. One patient in dose level 1, and one patient in dose level 2 experienced DLT (lipase > 5xULN, and neutrophils <500/μL respectively). However, dose level 3 (62Gy) was completed, with no DLTs in 3 patients. Overall, 56% of patients had a partial response and 28% showed stable disease according to RECIST. No signs of radiation induced liver disease (RILD). Two patients in dose level 3 experienced lymphocytopenia grade 4, with no clinical impact. Conclusion Conventionally fractionated radiotherapy of 58Gy to even large HCC was safe for patients with CPS A and B. 62Gy was delivered to three patients without any sign of clinically relevant increased toxicity. The maximum tolerated dose could not be determined. Trial registration ClinicalTrials.gov identifierNCT00777894, registered October 21st, 2008.